A case of diazoxide unresponsive congenital hyperinsulinemic hypoglycemia with missense mutation in ABCC8 gene - B. S., Nirmala; Handu, Kanika; S. , Lavanya; Kariyappa, Pushpalatha (International Journal of Contemporary Pediatrics, 2023)
Hypersecretion of insulin by pancreatic ß-cells causes hypoglycemia called congenital hyperinsulinism (CHI). It can inhibit brain development in infants. It is associated with mutations in the ABCC8 or KCNJ11 genes encoding for the SUR1 and KIR 6 (subunits of the ATP-sensitive potassium (KATP channel) a rare genetic disorder. It has an incidence rate of 1 in 50,000 in general populations and 1 in 2000 in areas with a higher rate of consanguinity. Here, we report a case of hyperinsulinemic hypoglycemia with ABCC8 gene mutation in a late preterm female infant who developed late-onset hypoglycemia. The infant developed hypoglycemic seizures on day 3 of life and her metabolic workup revealed hyperinsulinemia. A high glucose infusion rate and enteral feeding could not maintain the infant's serum glucose level. PET scan showed no abnormal somatostatin receptor avid lesion in pancreatic parenchyma. Hence genetic workup was done which showed a missense mutation in the ABCC8 gene which was c.4154C>G/p.Ser1385Cys. Over 9 months of follow-up, the infant is treated with octreotide and diazoxide, hasn't had any hypoglycemic events and has normal growth and psychomotor development for her age.